Clinical pathology accreditation: standards for the medical laboratory. Issue 10 (1st October 2002) - Burnett, D; Blair, C; Haeney, M R; Jeffcoate, S L; Scott, K W M; Williams, D L
Abstract : This article describes a new set of revised standards for the medical laboratory, which have been produced by Clinical Pathology Accreditation (UK) Ltd (CPA). The original standards have been in use since 1992 and it was recognised that extensive revision was required. A standards revision group was established by CPA and this group used several international standards as source references, so that the resulting new standards are compatible with the most recent international reference sources. The aim is to make the assessment of medical laboratories as objective as possible in the future. CPA plans to introduce these standards in the UK in 2003 following extensive consultation with professional bodies, piloting in selected laboratories, and training of assessors.